2014
DOI: 10.1007/s10162-014-0481-9
|View full text |Cite
|
Sign up to set email alerts
|

Cochlin in Normal Middle Ear and Abnormal Middle Ear Deposits in DFNA9 and Coch G88E/G88E Mice

Abstract: DFNA9 sensorineural hearing loss and vestibular disorder, caused by mutations in COCH, has a unique identifying histopathology including prominent acellular deposits in cochlear and vestibular labyrinths. A recent study has shown presence of deposits also in middle ear structures of DFNA9-affected individuals (McCall et al., J Assoc Res Otolaryngol 12:141-149, 2004). To investigate the possible role of cochlin in the middle ear and in relation to aggregate formation, we evaluated middle ear histopathology in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 41 publications
4
27
0
Order By: Relevance
“…This scenario is compatible with the evidence that chronic otitis media causes sensorineural hearing loss driven by inflammatory mediators in response to various endotoxins [Guo et al., ; Morizono et al., ; Paparella et al., , ]. Moreover, a recent study has reported that eosinophilic aggregates colocalized with cochlin staining are present in the middle ear of the p.G88E‐cochlin knock‐in mice [Robertson et al., ]. Cumulatively, these data suggest that cochlin may have an important role in the innate immune response within both middle and inner ear compartments.…”
Section: Discussionsupporting
confidence: 83%
“…This scenario is compatible with the evidence that chronic otitis media causes sensorineural hearing loss driven by inflammatory mediators in response to various endotoxins [Guo et al., ; Morizono et al., ; Paparella et al., , ]. Moreover, a recent study has reported that eosinophilic aggregates colocalized with cochlin staining are present in the middle ear of the p.G88E‐cochlin knock‐in mice [Robertson et al., ]. Cumulatively, these data suggest that cochlin may have an important role in the innate immune response within both middle and inner ear compartments.…”
Section: Discussionsupporting
confidence: 83%
“…Using a combination of physiological tests that assess cochlear function, here we demonstrate for the first time that Coch −/− mice have a small conductive hearing loss compared to Coch +/+ littermates, and possibly additional sensorineural component at the highest tested frequency. Together with the previously reported expression of cochlin in the murine and human middle ear, precisely on the articular surfaces of the incudomalleal and incudostapedial joints as well as pars tensa of the tympanic membrane (Robertson et al, 2014), we highlight cochlin's importance in sound conduction across the middle ear. In previous studies, a trend for increased ABR thresholds was present in young Coch −/− mice compared to Coch +/+ mice, although this trend did not reach the authors' criterion for significance (Choe et al, 2019).…”
Section: Discussionsupporting
confidence: 80%
“…This is the first description of the histopathology of the inner ear in this specific mutation. The histopathologic findings were similar to those previously described in other kinships (Table 1), both in the inner ear and in the extracochlear locations as previously described [McCall et al 2011; Robertson et al 2014]. Within the cochlea, the histopathologic findings include the diffuse loss of cellularity of the spiral ligament and an accumulation of an extracellular deposit in the spiral ligament, osseous spiral lamina and the limbus and the subepithelial mesenchymal tissue of the vestibular neuroepithelium.…”
Section: Discussionsupporting
confidence: 86%